Effect of Tax Revenue and Foreign Grants on Government Activities: A Study in Nepalese Perspective - Dahal, Arjun Kumar; Bhattarai, Ganesh; Budhathoki, Prem Bahadur (International Research Journal of MMC, 2024)
This study aims to examine the impact of previous years’ government expenditure, tax revenue, and foreign grants on determining Nepal's government activities or expenditures. The secondary data from used in the analysis. It includes 48 data points from 1974/75 to 2021/22, collected from the publication of Nepal Rastra Bank and economic surveys of Nepal. The descriptive and exploratory research designs are used in this study. Some statistical and econometric tools like descriptive statistics, Kolmogorov-Smirnov test, multiple regression analysis, analysis of variance (ANOVA), and residual analysis are used in this study. The previous expenditure determines the present government activities. Tax revenue, foreign grants, and previous years’ government expenditures are individually and jointly significant in determining the government expenditure. One unit increase in tax revenue and foreign grants resulted in a 0.177 and 0.046 unit increase in government expenditure in Nepal, respectively. 86.5 percent variation in government activities is determined by the previous year's government expenditure, tax revenue, and foreign grants. The positive impact of tax revenue is more than foreign grants on spending government activities. So, the policymakers must prioritize measures that increase domestic tax revenue.